Identification and Characterization of als Genes Involved in D-Allose Metabolism in Lineage II Strain of Listeria monocytogenes - Zhang, Lu; Wang, Yan; Liu, Dongxin; Luo, Lijuan; Wang, Yi; Ye, Changyun (Frontiers in Microbiology, 2018)
Listeria monocytogenes, an important food-borne pathogen, causes listeriosis and is widely distributed in many different environments. In a previous study, we developed a novel enrichment broth containing D-allose that allows better isolation of L. monocytogenes from samples. However, the mechanism of D-allose utilization by L. monocytogenes remains unclear. In the present study, we determined the metabolism of D-allose in L. monocytogenes and found that lineage II strains of L. monocytogenes can utilize D-allose as the sole carbon source for growth, but lineage I and III strains cannot. Transcriptome analysis and sequence alignment identified six genes (lmo0734 to 0739) possibly related to D-allose metabolism that are only present in the genomes of lineage II strains. Recombinant strain ICDC-LM188 containing these genes showed utilization of D-allose by growth assays and Biolog phenotype microarrays. Moreover, lmo0734 to 0736 were verified to be essential for D-allose metabolism, lmo0737 and 0738 affected the growth rate of L. monocytogenes in D-allose medium, while lmo0739 was dispensable in the metabolism of D-allose in L. monocytogenes. This is the first study to identify the genes related to D-allose metabolism in L. monocytogenes, and their distribution in lineage II strains. Our study preliminarily determined the effects of these genes on the growth of L. monocytogenes, which will benefit the isolation and epidemiological research of L. monocytogenes.